Evaluation of an In-house indirect ELISA for detection of antibody against haemorrhagic septicemia in Asian elephants - Tankaew, Pallop; Singh-La, Thawatchai; Titaram, Chatchote; Punyapornwittaya, Veerasak; Vongchan, Preeyanat; Sawada, Takuo; Sthitmatee, Nattawooti (Journal of Microbiological Methods, 2017)
Pasteurella multocida causes haemorrhagic septicemia in livestock and wild animals, including elephants. The disease has been reported in Asian elephants in India and Sri Lanka, but to date there have been no reported cases in Thailand. ELISA or indirect hemagglutination assays (IHA) have been demonstrated to be able to detect the antibody against the disease in cattle, but no data are available for elephants. The present study reports a novel in-house indirect ELISA for antibody detection of haemorrhagic septicemia in Asian elephants, and evaluates the sensitivity and specificity of the method using a Bayesian approach. The characteristics of ELISA and IHA were analyzed using a one population Bayesian model assuming conditional dependence between these two diagnostic tests. The IHA was performed as recommended by the World Organization for Animal Health (OIE) manual for haemorrhagic septicemia. An in-house indirect ELISA was developed with a heat extract antigen of P. multocida strain M-1404 (serovar B:2) as a coating antigen and rabbit anti-immunoglobulin G conjugated with horseradish peroxidase (eIgG-HRP). The checkerboard titration method was done using elephant sera immunized with P. multocida bacterin and negative sera from colostrum-deprived elephant calves. The concentrations of heat extract antigen (160μg/ml), sample serum (1:100), and eIgG-HRP (1:1000) were optimal for the assay. The calculated cut-off value was 0.103. Of the elephant sera, 50.59% (43/85) were considered seropositive by ELISA. The sensitivity of the ELISA test was higher than that of the IHA test [median=86.5%, 95% posterior probability interval (PPI)=52.5–98.9%] while the specificity was lower (median=54.1%, PPI=43.6–64.7%). The median sensitivity and specificity of IHA were 80.5% (PPI=43.8–98.0%) and 78.4% (PPI=69.0–87.0%), respectively. These findings suggest that our in-house indirect ELISA can be used as a tool to detect the antibody against haemorrhagic septicemia in Asian elephants. •An indirect ELISA for antibody detection of haemorrhagic septicemia in Asian elephants was successfully developed.•Heat extract antigen 160µg/ml, a dilution of 1:100 of sample serum, and eIgG-HRP 1:1000 were optimal concentrations.•The calculated cut-off value was 0.103.•The sensitivity of the ELISA test was higher than that of the IHA test while the specificity was lower.•The median sensitivity and specificity of IHA were 80.5% (PPI = 43.8-98.0%) and 78.4% (PPI= 69.0-87.0%).